Leniency in EU competition law - Halvorsen Barlund, Ingrid Margrethe (International competition law series ;, 2020)
Leniency in EU Competition Law' provides a comprehensive analysis of the leniency procedure in the European Union (EU) cartel enforcement. Applications for lenient treatment by whistleblowers are an essential feature of cartel enforcement. Leniency has emerged as one of the main enforcement instruments used by competition authorities to combat cartels. Offering immunity from punishment is believed to destabilise the already existing cartels and deter undertakings from entering into such arrangements. This book offers the first in-depth analysis of the scope of leniency in EU competition law, considering three crucial ramifications , ensuring a leniency applicant can self-report with confidence, retaining the right to compensation of those who have suffered losses due to the cartel and furthering the objective of undistorted competition within the internal market.